2001
DOI: 10.1128/aac.45.11.3246-3249.2001
|View full text |Cite
|
Sign up to set email alerts
|

Novel Tetracycline Resistance Gene, tet (32), in the Clostridium -Related Human Colonic Anaerobe K10 and Its Transmission In Vitro to the Rumen Anaerobe Butyrivibrio fibrisolvens

Abstract: A novel tetracycline resistance gene, designated tet(32), which confers a high level of tetracycline resistance, was identified in the Clostridium-related human colonic anaerobe K10, which also carries tet(W). tet(32) was transmissible in vitro to the rumen anaerobe Butyrivibrio fibrisolvens 2221 R . The predicted gene product of tet(32) has 76% amino acid identity with Tet(O). PCR amplification indicated that tet(32) is widely distributed in the ovine rumen and in porcine feces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
61
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 21 publications
2
61
0
Order By: Relevance
“…These genes could represent a core antibiotic resistome for this cohort of swine. Indeed, it was suggested that tet(32) is abundant in farm animals (28), and our data support that conclusion for swine. The constant selective pressure of 50 y of in-feed antibiotics appears to have established a high background level of resistance in the swine microbiome.…”
Section: Discussionsupporting
confidence: 80%
“…These genes could represent a core antibiotic resistome for this cohort of swine. Indeed, it was suggested that tet(32) is abundant in farm animals (28), and our data support that conclusion for swine. The constant selective pressure of 50 y of in-feed antibiotics appears to have established a high background level of resistance in the swine microbiome.…”
Section: Discussionsupporting
confidence: 80%
“…The gene tet(32) was identified in the Clostridiumrelated human colonic anaerobe bacterium K10, which also carried tet(W) (Melville et al, 2001).…”
Section: Ribosomal Protectionmentioning
confidence: 99%
“…There have been several reports on the isolation of plasmids from rumen bacterial isolates and the transfer of genes between rumen microbes (16)(17)(18)(19)(20)(21)(22)(23)(24). Plasmids isolated from rumen bacteria have been characterized as having replication and mobilization functions, and some contain accessory genes (25)(26)(27)(28).…”
mentioning
confidence: 99%